Posthuman performativity, gender and "school bullying": Exploring the material-discursive intra-actions of skirts, hair, sluts, and poofs - Jessica Ringrose; Victoria Rawlings (Linköping University Electronic Press, 2015)
In this article we take off from critiques of psychological and school bullying typologies as creating problematic binary categories of bully and victim and neglecting sociocultural aspects of gender and sexuality. We review bullying research informed by Judith Butler's theories of discursive performativity, which help us to understand how subjectification works through performative repetitions of heterosexual gender norms. We then build on these insights drawing on the feminist new materialist approach of Karen Barad's posthuman performativity, which we argue enlarges our scope of inquiry in profound ways. Barad's theories suggest we move from psychological models of the inter-personal, and from Butlerian notions of discursive subjectification, to ideas of discursive-material intra-action to consider the more-thanhuman relationalities of bullying. Throughout the article, we demonstrate the approach using examples from qualitative research with teens in the UK and Australia, exploring nonhuman agentic matter such as space, objects and time as shaping the constitution of gender and sexual bullying events. Specifically we examine the discursive-material agential intraactions of skirts and hair through which 'girl' and 'boy' and 'slut' and 'gay' materialise in school spacetimematterings. In our conclusion we briefly suggest how the new materialism helps to shift the frame of attention and responses informing gendered intraactions in schools.